2017
DOI: 10.3389/fnmol.2017.00366
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Quantum Brain Hypothesis: Toward Quantum (Neuro)biology?

Abstract: The nervous system is a non-linear dynamical complex system with many feedback loops. A conventional wisdom is that in the brain the quantum fluctuations are self-averaging and thus functionally negligible. However, this intuition might be misleading in the case of non-linear complex systems. Because of an extreme sensitivity to initial conditions, in complex systems the microscopic fluctuations may be amplified and thereby affect the system’s behavior. In this way quantum dynamics might influence neuronal com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 100 publications
(119 reference statements)
2
61
0
Order By: Relevance
“…The use of a quantum framework to accurately describe human behaviour does not necessarily mean that this behaviour results from quantum effects in neural processes. A clearer understanding of these processes, however, could also elucidate to what extent quantum physics is involved in the emergence of cognition from neural activity 10 . Should it turn out that experimental evidence supports hypotheses of quantum enhanced neural processing we might turn this knowledge towards thinking about how we think.…”
Section: Discussionmentioning
confidence: 99%
“…The use of a quantum framework to accurately describe human behaviour does not necessarily mean that this behaviour results from quantum effects in neural processes. A clearer understanding of these processes, however, could also elucidate to what extent quantum physics is involved in the emergence of cognition from neural activity 10 . Should it turn out that experimental evidence supports hypotheses of quantum enhanced neural processing we might turn this knowledge towards thinking about how we think.…”
Section: Discussionmentioning
confidence: 99%
“…The above arguments suggest some sort of holographic physical system in the brain, like a superfluid, but how could such a state of matter occur there? There have been a number of recent proposals that argue for quantum effects in the brainfor a review see (Jedlicka, 2017). However, calculations have demonstrated that fast decoherence rates should be expected in such an environment (Tegmark, 1999) and that flies in the face of highly entangled systems like superfluids.…”
Section: Biological Plausibilitymentioning
confidence: 99%
“…Of course, a means of interaction between the superfluid and a macroscopic system of neurons would be required. The amplification of quantum level effects to the macro scale has been proposed before via the neurological mechanism of cellular ion channels (Vaziri, 2010;Jedlicka, 2017). These are individual proteins that only allow a single ion to pass into or out of neurons at a time and are small enough to be influenced by quantum scale effects, yet able to affect neuron firing rates at macro scales and vice-versa.…”
Section: Biological Plausibilitymentioning
confidence: 99%
“…However, a growing body of literature has recently demonstrated that quantum coherence in living organisms exists and it is itself essential for their functioning (e.g., [21,22]). With the recent rise of the field of quantum biology, it has been suggested that quantum phenomena might also influence brain activity and affect its cognition [23]. However, it is important to consider the brain itself as a non-linear dynamical complex system, whose activity may vary if the system changes [23].…”
mentioning
confidence: 99%
“…With the recent rise of the field of quantum biology, it has been suggested that quantum phenomena might also influence brain activity and affect its cognition [23]. However, it is important to consider the brain itself as a non-linear dynamical complex system, whose activity may vary if the system changes [23]. As a consequence, these quantum fluctuations that arise from the interaction between the brain and the heart would be highdimensional, and thus, the complexity of the system (i.e., its ability to adapt and function in an ever-changing environment) would also be high-dimensional [24].…”
mentioning
confidence: 99%